1987
DOI: 10.1111/j.1365-2362.1987.tb01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Seeking clues for a positive diagnosis of the irritable bowel syndrome

Abstract: Despite its high prevalence the irritable bowel syndrome (IBS) lacks acceptable pathophysiological markers and its diagnosis largely depends on the exclusion of underlying organic disease. Systemic acid-base balance, serum electrolytes and the composition of faecal water (electrolytes and organic anions), were studied in thirty-eight diarrhoeal patients out of a series of ninety-three consecutive IBS patients. Only patients with diarrhoea as the predominant symptom were included in the study to evaluate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…SCFAs, as the main metabolites of the gut microbiota, and 5-HT, as an important regulatory factor of the brain-gut axis, may be involved in the abnormal BGM axis of IBS. Alterations in SCFAs in feces and 5-HT in blood have been found in IBS patients in some studies [27,28,[30][31][32]. This is the first meta-analysis to explore the alterations in SCFAs and 5-HT in IBS, and some interesting findings were observed in our meta-analysis.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…SCFAs, as the main metabolites of the gut microbiota, and 5-HT, as an important regulatory factor of the brain-gut axis, may be involved in the abnormal BGM axis of IBS. Alterations in SCFAs in feces and 5-HT in blood have been found in IBS patients in some studies [27,28,[30][31][32]. This is the first meta-analysis to explore the alterations in SCFAs and 5-HT in IBS, and some interesting findings were observed in our meta-analysis.…”
Section: Discussionsupporting
confidence: 62%
“…Tana et al [25] found that levels of acetic acid, propionic acid, and total SCFAs were significantly higher in IBS patients than in controls. These findings were [28]. However, Kopecny et al [27] found that the fecal SCFAs of IBS patients were characterized by lower levels of total SCFAs, acetic acid, and propionic acid and by higher levels of butyric acid.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The colonic exploration as part of the initial work-up of the IBS patient is unclear: authors like Van Der Horst et al [6] believe that a routine contrast enema or colonos copy are unnecessary and that they may increase the anxi ety of the patients, while others, including Schuster [7], advise these examinations to exclude structural abnor malities, in the first place cancer, to reassure the patients and to contribute to a confident therapeutic relationship. Even further going, Vernia et al [8] showed that in patients with suspected IBS and unusual diarrhoea, a clin ical diagnosis of IBS complemented with routine bio chemical testing and examination of the whole colon may not be enough to exclude reliably organic causes of diar rhoea and recommend more extensive investigations in this subgroup of IBS patients.…”
mentioning
confidence: 99%